2016
DOI: 10.1111/eea.12449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought stress on oviposition preference and offspring performance of the lace bugCorythucha marmorataon its goldenrod host,Solidago altissima

Abstract: Stress and vigor are endpoints on a continuum of the suitability of plants for insect herbivores. Senescence-feeding insects, such as the chrysanthemum lace bug, Corythucha marmorata (Uhler) (Hemiptera: Tingidae, Tingitini), are hypothesized to benefit from any stressor hastening the senescence of plant tissues, such as drought. They are also hypothesized to prefer feeding and ovipositing on stressed plants, due to increased performance of themselves and their offspring. We conducted choice and no-choice field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 56 publications
0
18
0
1
Order By: Relevance
“…Except for leaf toughness, this result may also be explained by a higher content of secondary metabolites in the drought-stressed plants (Prill et al, 2014). Drought-stress plants were also preferred by a range of other herbivore species (Meyer et al, 2006;Neto et al, 2012;Helmberger et al, 2016). The results on herbivore preference for watered plants, however, contrast with the results of Gutbrodt et al (2011), demonstrating that generalist S. littoralis preferred drought-stressed plants due to fewer secondary metabolites in these plants.…”
Section: Effects Of Droughtmentioning
confidence: 96%
See 1 more Smart Citation
“…Except for leaf toughness, this result may also be explained by a higher content of secondary metabolites in the drought-stressed plants (Prill et al, 2014). Drought-stress plants were also preferred by a range of other herbivore species (Meyer et al, 2006;Neto et al, 2012;Helmberger et al, 2016). The results on herbivore preference for watered plants, however, contrast with the results of Gutbrodt et al (2011), demonstrating that generalist S. littoralis preferred drought-stressed plants due to fewer secondary metabolites in these plants.…”
Section: Effects Of Droughtmentioning
confidence: 96%
“…more secondary metabolites in drought-stressed plants, this may also mean that the effect of drought stress on the content of secondary metabolites depends on the plant species and/or metabolite studied. Drought-stress plants were also preferred by a range of other herbivore species (Meyer et al, 2006;Neto et al, 2012;Helmberger et al, 2016). Meyer et al (2006) suggested that this preference may be caused by higher concentrations of proline and non-structural carbohydrates in the leaves.…”
Section: Effects Of Droughtmentioning
confidence: 99%
“…Instead, analyses involving factors such as insect developmental stage and host tissue age, would provide a clearer picture of the overall usefulness of this unified plant stress/vigor hypothesis. Unfortunately, experimental tests typically do not include these factors in their design (for example, see Krugner et al 2009, Mody et al 2009, Paine and Hanlon 2010, Gutbrodt et al 2011, Simpson et al 2012, Tariq et al 2012, Banfield-Zanin and Leather 2015a, b, Couture et al 2015, Dardeau et al 2015, Brewer et al 2016, Helmberger et al 2016, Pineda et al 2016, Valim et al 2016, even though such elements are central to this unified hypothesis.…”
Section: Weevil Dynamics Support a Unified Plant Stress/vigor Hypothesismentioning
confidence: 99%
“…An alternative explanation for the difference in covariance of resistance on US plants in US and Japanese gardens is that difference in the lace bug phenology between locations may cause difference in plant quality caused by other insect herbivory. Helmberger, Craig, and Itami () reported that lace bugs perform better on drought‐stressed S. altissima due to mobilization of structural nitrogen increasing the nutritional quality of stressed tissues. In addition to drought stress, stress from early herbivory may positively affect lace bug performance, as early herbivory has been reported to increase nitrogen and increase herbivory by later herbivores (Danell & Huss‐Danell, ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why a positive genetic covariance was detected in US plants in US garden is unclear; however, since there were no differences in the G-matrices between plant origins within the US gardens it is unlikely that this positive value has ecological TA B L E 2 Observed scale G-matrices for resistance indices of S. altissima obtained from the 1,000 samples of posterior distribution of the MCMC analyses of (a) US plants in US gardens, (b) US plants in Japanese gardens, (c) Japanese plants in US gardens, and (d) An alternative explanation for the difference in covariance of resistance on US plants in US and Japanese gardens is that difference in the lace bug phenology between locations may cause difference in plant quality caused by other insect herbivory. Helmberger, Craig, and Itami (2016) reported that lace bugs perform better on droughtstressed S. altissima due to mobilization of structural nitrogen increasing the nutritional quality of stressed tissues. In addition to drought stress, stress from early herbivory may positively affect lace bug performance, as early herbivory has been reported to increase nitrogen and increase herbivory by later herbivores (Danell & Huss-Danell, 1985).…”
Section: Negative Genetic Covariance Between Plant Resistances To Dmentioning
confidence: 99%